Analisis Faktor Penyebab Kejadian Hipertensi di Wilayah Puskesmas Beji Depok: Analysis of factors causing the incidence of hypertension in the Beji Depok Community Health Center area - Asri, Intan Puspita; Putri, Anna Maryanah; Afifah, Faidah; Khairunnisa, Aisyah; Salamah, Nurul Pitriani; Putri Nabila, Shofia; Kusumastuti, Istiana (MPI Press, 2023)
Background: Hypertension is one of the non-communicable diseases often referred to as